EDUCATION, CLASS, AND FEMALE BODILY AUTONOMY IN AHDAF SOUEIF’S "IN THE EYE OF THE SUN" AND FADIA FAQIR’S "MY NAME IS SALMA" - Al-Mohammedi, Galal; Osman, Sharifah Aishah; Somiah, Vilashini (SARJANA, 2025)
This article examines how education and class intersect to shape female bodily autonomy in two novels by Arab diasporic authors, Ahdaf Soueif’s In the Eye of the Sun and Fadia Faqir’s My Name is Salma. Through comparative feminist analysis, it explores how the protagonists’ bodies are inscribed with cultural meaning and regulated by social hierarchies. Rather than portraying education or social mobility as inherently liberatory, the novels reveal their limitations in the absence of critical agency and emotional resilience. Asya’s intellectual privilege contrasts with Salma’s restricted access to formal learning, yet both narratives show how class mediates bodily control and access to selfhood. The article argues that female bodily autonomy in these texts is not achieved through structural advantages alone, but through the protagonists’ capacity to narrate, reflect, and contest imposed roles. Drawing on feminist literary and cultural frameworks, the analysis of the two novels challenges reductive views of empowerment, presenting bodily autonomy instead as a process of reclamation forged in tension with patriarchal and class-based constraints.